NCOG-07. FEATURES OF EPILEPTOGENIC BRAIN METASTASES AND THEIR TREATMENT. (9th November 2020) - Musgrave, Nicholas; Huntoon, Kristin; Wang, Joshua; Hardesty, Douglas; Prevedello, Daniel; Lonser, Russell; Elder, Bradley
Abstract: Patients with brain metastases (BM) may experience seizures at diagnosis or during their treatment. Seizures are associated with decreased overall survival (OS) and poorer quality of life. Therapeutic options may include surgical resection of epileptogenic BM. This study evaluated features of epileptogenic BM and whether surgical resection of these tumors improved seizure control and OS. A retrospective single-center review between 2006-2016 identified 1581 patients with BM. Data analyzed included demographics, primary cancer, systemic treatments, radiographic features of BM, BM treatment modalities, anti-epileptic drugs (AEDs), and seizure characteristics before and after intervention for BM. Chi-squared tests were used for categorical variables. Kaplan-Meier curves and Breslow values were used to assess OS following seizure. Of 1581 patients with BM, 136 (9%) experienced one or more seizures. Seizure was the presenting symptom of BM in 74 (54.4%) patients. Melanoma metastases were most epileptogenic, causing seizure in 38 of 216 (17.6%) patients (p< 0.001). Frontal lobe metastases were most common in patients with seizures (100, 73.5% p=0.033). After median follow-up of 23 months, 48 of 80 (60%) surgical patients were seizure free compared with 27 of 56 (48.2%) non-surgical patients. OS from first seizure was improved in surgical patients versus non-surgical patients (735±133 vs 447±74 days, p=0.043). Frontal lobe tumor resection (n=61) conferred improved survival compared with non-frontal lobe tumor resections (n=19) (698±323 vs 344±132 days, p=0.044). Variables such as demographics, number of BM, tumor histology, and dose of AED were not significantly different between surgical and non-surgical groups. Seizures due to BM cause significant morbidity and mortality. Frontal lobe location and melanoma histology increase seizure risk. Resection of BM was associated with improved seizure control and prolonged OS from the time of first seizure. Further studies should delineate the impact of surgery and determine if a specific constellation of variables warrants prophylactic AEDs.